ChemInform Abstract: A Review of Molybdenum Adsorption in Soils/Bed Sediments: Speciation, Mechanism, and Model Applications. Issue 30 (29th July 2014) - Xu, Nan; Braida, Washington; Christodoulatos, Christos; Chen, Jianping
Abstract Review: 103 refs.